Monopoly Edutainment Media and its Implementation Through the Course Review Horay Model in Learning to Write Indonesian - Ida Ayu Gede Purna Astiti; Putu Aditya Antara; Kadek Yudiana (Jurnal Pedagogi dan Pembelajaran, 2023)
The low ability of students to write is due to teachers' need for more use of learning media during the learning process. So to overcome these problems, we need media to help the student learning process. This research aims to develop edutainment monopoly media and its implementation through the course review horay model. This research belongs to the type of development research which was developed using the ADDIE model. The ADDIE model comprises five research stages: analysis, design, development, implementation, and evaluation. The subjects of this study were two learning material experts and two learning media experts. The test subjects included two teachers, three individual students, and six small group test students. Methods of data collection using test and nontest methods. The data collection instrument used questionnaires and test questions. The techniques used in collecting data are descriptive quantitative analysis, qualitative, and inferential statistics. The study's results, namely assessments from content and learning media experts, obtained very good qualifications. The test results for the two teacher responses scored 91.7% (very good). The results of student responses were 91.94% (very good). The practicality test results scored 99.7% (very practical). The individual trial results were 93.6 (very good). The results of the small group trials were 91% (very good). The t-test results showed significant differences before and after using edutainment monopoly media and its implementation through the course review horay model. Based on these results, monopoly edutainment media and its implementation through the course review horay model can improve students' writing skills.